2018
DOI: 10.15294/jdm.v9i1.14647
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Cash Holdings in Developed and Developing Countries

Abstract: This paper aims to find out the determinants of amount of cash holdings in developed and developing countries. One of the reason is because majority of studies that exist only focus on developed countries such as US or UK. Therefore, it is important to study cash holdings in the context of developing countries as well. Samples are drawn from DataStream Database using a sample period between 2009-2014 by including recent output with firm selection criterion based on data availability of firms (Al-Najjar, 2013),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
2
6
0
2
Order By: Relevance
“…This result is contrary to the results of research by [9] which shows that board independence has a negative relationship and a significant effect on cash holding. The results of this study are in accordance with the results of a study conducted by [10] showing board independence has no influence on cash holding and research results from [11].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result is contrary to the results of research by [9] which shows that board independence has a negative relationship and a significant effect on cash holding. The results of this study are in accordance with the results of a study conducted by [10] showing board independence has no influence on cash holding and research results from [11].…”
Section: Discussionsupporting
confidence: 91%
“…The results of this study contradict the results of [9] study which showed a negative relationship to cash holding and the results of research by [10] which said the board size had a significantly positive relationship to cash holding. The results of the research that are in accordance with the results of this study are the studies conducted by [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As examined by recent literature, the board of directors is an essential component of corporate governance [41,73], particularly in substantial business enterprises [84]. e internal governance is ordinarily estimated by ownership structure, nonexecutive directors on board, effective audit, and so forth [85,86].…”
Section: Board Financial Expertise (Bfe) and Cash Holdingmentioning
confidence: 99%
“…e vast body of literature on corporate board and firm's governance characterized board obligations into different roles [52,53,84,85]. ese roles are not fundamentally distinct, and each one is fortified with an expert financial presence on board.…”
Section: Board Financial Expertise (Bfe) and Cash Holdingmentioning
confidence: 99%